Radiosensitivity of patient-derived glioma stem cell 3-dimensional cultures to photon, proton, and carbon irradiation - Chiblak, Sara; Tang, Zili; Campos, Benito; Gál, Zoltán; Unterberg, Andreas; Debus, Jürgen; Herold-Mende, Christel; Abdollahi, Amir (International journal of radiation oncology, biology, physics, 2016)
Purpose To investigate the radiosensitivity of primary glioma stem cell (GSC) cultures with different CD133 status in a 3-dimensional (3D) model after photon versus proton versus carbon irradiation. Methods and Materials Human primary GSC spheroid cultures were established from tumor specimens of six consented glioblastoma patients. Human U87MG was used as a classical glioblastoma radioresistant cell line. Cell suspensions were generated by mechanical dissociation of GSC spheroids and embedded in a semi-solid 3D matrix before irradiation. Spheroid-like colonies were manually counted by microscopy. Cells were also recovered and quantified by fluorescence. CD133 expression and DNA damage were evaluated by flow cytometry. Results The fraction of CD133 cells varied between 0.014% and 96% in the six GSC cultures and showed a nonsignificant correlation with plating efficiency and survival fractions. The 4 most photon-radioresistant GSC cultures were NCH644, NCH421k, NCH441, and NCH636. Clonogenic survival for proton irradiation revealed relative biologic effectiveness (RBE) in the range of 0.7-1.20. However, carbon irradiation rendered the photon-resistant GSC cultures sensitive, with average RBE of 1.87-3.44. This effect was partly attributed to impaired capability of GSC to repair carbon ion-induced DNA double-strand breaks as determined by residual DNA repair foci. Interestingly, radiosensitivity of U87 cells was comparable to GSC cultures using clonogenic survival as the standard readout. Conclusions Carbon irradiation is effective in GSC eradication with similar RBE ranges approximately 2-3 as compared with non-stem GSC cultures (U87). Our data strongly suggest further exploration of GSC using classic radiobiology endpoints such as the here-used 3D clonogenic survival assay and integration of additional GSC-specific markers.